Alexander Williamson and the Modernisation of Japan. (September 2015) - Davies, Alwyn G.
One hundred and fifty years ago, five students were smuggled out of feudal Japan and came to London to learn Western technology, governance, and economics. They were put into the care of Alexander Williamson, who was Professor of Chemistry at University College London, and when they went back they, and the students who followed them, became the founders of the modern Japanese state. This is the British side of that remarkable story. Williamson's career and chemistry are briefly reviewed, followed by an account of the students' presence in Britain, and then the commemoration of the sesquicentenary of these events.